Combined analysis of metabolome and transcriptome of wheat kernels reveals constitutive defense mechanism against maize weevils - Lv, Liangjie; Guo, Xiaorui; Zhao, Aiju; Liu, Yuping; Li, Hui; Chen, Xiyong (Frontiers in Plant Science, 2023)
Sitophilus zeamais (maize weevil) is one of the most destructive pests that seriously affects the quantity and quality of wheat (Triticum aestivum L.). However, little is known about the constitutive defense mechanism of wheat kernels against maize weevils. In this study, we obtained a highly resistant variety RIL-116 and a highly susceptible variety after two years of screening. The morphological observations and germination rates of wheat kernels after feeding ad libitum showed that the degree of infection in RIL-116 was far less than that in RIL-72. The combined analysis of metabolome and transcriptome of RIL-116 and RIL-72 wheat kernels revealed differentially accumulated metabolites were mainly enriched in flavonoids biosynthesis-related pathway, followed by glyoxylate and dicarboxylate metabolism, and benzoxazinoid biosynthesis. Several flavonoids metabolites were significantly up-accumulated in resistant variety RIL-116. In addition, the expression of structural genes and transcription factors (TFs) related to flavonoids biosynthesis were up-regulated to varying degrees in RIL-116 than RIL-72. Taken together, these results indicated that the biosynthesis and accumulation of flavonoids contributes the most to wheat kernels defense against maize weevils. This study not only provides insights into the constitutive defense mechanism of wheat kernels against maize weevils, but may also play an important role in the breeding of resistant varieties.